Airborne measurements of surface albedo and leaf area Index of snow‐covered boreal forest - Manninen, Terhikki; Roujean, Jean‐Louis; Hautecoeur, Olivier; Riihelä, Aku; Lahtinen, Panu; Jääskeläinen, Emmihenna; Siljamo, Niilo; Anttila, Kati; Sukuvaara, Timo; Korhonen, Lauri (John Wiley & Sons, 2022)
Abstract Helicopter based simultaneous measurements of broadband surface albedo and the effective leaf area index (LAIeff) were carried out in subarctic area of Finnish Lapland in spring 2008, 2009, and 2010 under varying illumination and snow cover conditions. Vertical profile measurements show that the found relationship between albedo and LAIeff seems to be rather independent of the flight altitude and therefore the footprint scale. Actually, flights above 500 m in altitude revealed low variations of the surface albedo approaching an aerial average at 1 km, meaning that a footprint of 20 km is representative of the landscape. The albedo of the area was beta distributed, and without LAIeff values below 0.25, the average albedo value of the area would decrease from 0.49 to 0.44 showing the albedo sensitivity to sparse vegetation. The results agreed with the photon recollision probability based model PARAS and the MODIS satellite albedo product MCD43A3. However, differences between satellite based and airborne albedo values were noticed, which could be explained by a difference in footprint size and/or the strong local heterogeneity as certain flights were operated on specific targets. Key Points • Surface albedo and effective leaf area index (LAI) can be measured at fine resolution and landscape scale simultaneously using helicopter • Surface albedo and effective LAI are coherently retrieved based on a photon recollision probability based model • Airborne and satellite-based surface albedo show a good agreement Plain Language Summary Helicopter based measurements were used to assess how much a forest stand laying over a snow slab reduces the surface albedo at high latitudes where the sun zenith angle is large and shadow cast is always important. The effect is amplified in the case of sparse vegetation as there is less mutual shadowing. Model results and satellite observations are found in good agreement with the airborne data sets.